Performing the township: pantsula for life - Van Niekerk, Heather Elizabeth (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 2018)
Pantsula dance is a performing art born from the townships of Johannesburg. It is a dance form performed across South Africa, in a variety of contexts; in theatres, music videos and competitions in community halls, on national and international stages and on television, and in the streets of townships, cities and suburbs across South Africa and abroad. Its performance is widespread, but it has its beginnings as a dance form born in areas created to marginalise and oppress. There is a scarcity of academic scholarship related to pantsula dance. This thesis aims to be a contribution to that pre-existing body of knowledge in the hope that there can be further engagement on this important, and increasingly mainstream, art form. I have focused my thesis on analysing pantsula dance as a performance of 'the township'. This has been attempted through an ethnographic engagement with pantsula dancers based in different township areas of Johannesburg and Graha mstown: various members of Impilo Mapantsula, Via Katlehong, Intellectuals Pantsula, Via Kasi Movers, Dlala Majimboz and the cast of Via Katlehong's Via Sophiatown. The research was conducted between 2013 and 2016 and serves to represent various moments within the ethnographic research process, while coming to understand various aspects of pantsula dance. An engagement with notions of 'the township', the clothing choices of the pantsula 'uniform', the core moves, inherent hybridity in the form itself, and the dedication to the dance form as a representation of the isipantsula 'way of life', are addressed throughout the thesis. As well as engaging with the memory and representation of Sophiatown as an important component to pantsula dance. Pantsula dance, an intrinsically South African dance form, provides a celebratory conception of 'the township' space and allows people from different backgrounds to engage in an important part of South Africa's past, present and future.
Keywords: Pantsula (Dance) -- South Africa Johannesburg; Pantsula (Dance) -- South Africa -- Makhanda; Dance Social aspects -- South Africa; Sophiatown (Johannesburg, -- South Africa)